Profit Sharing System for Drift Gill Net Fishermen in Bagan Hulu Village, Bangko District, Rokan Hilir Regency, Riau Province - Malau, Ira Mawar; Sofyani, Tince; Hendrik, Hendrik (Jurnal Perikanan dan Kelautan, 2024)
This research was conducted in Bagan Hulu Village, Bangko District, Rokan Hilir Regency, Riau Province on November 21 - December 09, 2022, to analyze the profit-sharing system for drift gill net fishermen and compare the profit-sharing system that applies in Bagan Hulu Village with the Law No.16 of 1964 concerning profit sharing. The method used was a survey with a total sample of 32 fisherman owners; the sampling technique was simple random sampling. The results showed that the profit-sharing system for drift gill net fishermen in Bagan Hulu Village, Bangko District, Rokan Hilir Regency, Riau Province, uses a local profit-sharing system by sharing profits after deducting production costs with a percentage of 60% for fisherman owners and 40% for labor fishermen provided that all operational costs are shared. From a comparison of the profit-sharing system according to UUBHP, the share of income for fishermen who own drift gill nets in Bagan Hulu Village is greater than that according to UUBHP. The difference can be seen from the joint costs incurred. In the law, the shared costs incurred are consumption, while in the Bagan Hulu Village, the shared costs incurred are all operational costs